The impact of centralization on the performance of health organizations: an empirical study on Yadmah General Hospital in Najran - Alfataih, Masoud Turki Ali; Alfataih, Mohmad Turki Hamad; Hadi, Mohmad Shadad; Alrasheed, Hezam Fahad; Alqashanin, Nasser Mohammad; Al-Yami, Mohammed Mahdi Jarallah (Journal of Economic, Administrative and Legal Sciences, 2022)
The importance of health organizations is a top priority that governments seek to achieve because of their social and humanitarian goals and to preserve the health of citizens, despite the importance of decentralization and its role in improving administrative work in hospitals; However, Yadmah General Hospital in Najran still suffers from centralization, especially in situations that require good behavior and urgent decisions.Based on the foregoing, the current study aims to identify the impact of centralization in its various forms (financial, administrative, and organizational) on the level of performance in Yadmah General Hospital. To achieve the objectives of the study, the researcher used the descriptive analytical method in preparing the study, in addition to using the questionnaire tool in collecting data from the study sample members, as the current study will be applied to a sample of (312) employees working in Yadmah General Hospital. The researcher will also use a program (SPSS) in the data analysis process.After collecting and analyzing the data, the following conclusions were drawn: Centralization with its various dimensions (financial, administrative, and organizational) exists to a moderate degree in Yadmah General Hospital in Najran region, from the point of view of the study sample members with a relative weight of (67.0%). There is an effective performance level for Yadmah General Hospital in Najran region from the point of view of the employees working in the hospital. There is a statistically significant relationship at the significance level (α ≤ 0.05) for the presence of centralization (administrative, financial, and organizational) and the level of performance effectiveness of Yadmah General Hospital in Najran with correlation coefficients amounting to (0.315, 0.218, 0.212), respectively. In light of these results, the researcher made a number of recommendations, the most important of which are the following: Conflicts between financial management and staff within the hospital due to financial factors (such as bonuses and salaries) must be resolved. the necessity of activating the role of oversight over the administrative units within the hospital. Authority should be delegated between the different administrative levels, and attention should be paid to empowering employees.
Keywords: Health Organizations; Hospital administration; Central Administration; Yedamah General Hospital